Prophets male and female : gender and prophecy in the Hebrew Bible, the Eastern Mediterranean, and the ancient Near East - Stökl, Jonathan, 1977-; Carvalho, Corrine L. (Ancient Israel and its literature, 2013)
"Because gender is an essential component of societies of all times and places, it is no surprise that every prophetic expression in the ancient social world was a gendered one. In this volume scholars of the biblical literature and of the ancient Mediterranean consider a wide array of prophetic phenomena. In addition to prophetic texts of the Hebrew Bible, the essays also look at prophecy in ancient Mesopotamia and early Christianity. Using the most current theoretical categories, the volume demonstrates how essential a broad definition of gender is for understanding its connection to both the delivery and the content of ancient prophecy. Attention to gender dynamics will continue to reveal the fluidity of prophetic gender performance and to open up the ancient contexts of prophetic texts."--